2016
DOI: 10.5588/ijtld.15.0535
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of Xpert® MTB/RIF testing in Mozambique: results of programmatic implementation of GxAlert

Abstract: Remote monitoring of diagnostic platforms is feasible in LMICs. While promising, this effort needs to address issues around patient data ownership, confidentiality, interoperability, unique patient identifiers, and data security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…A preliminary study from South Africa 151 found that Xpert MTB/RIF probe information, which differed substantially by geographical region, could be used for near real-time national surveillance using connected software, such as GXalert (open-source data connectivity for the GeneXpert). 152 By documenting the increasing frequency of a specific mutation, these data could be used for identifying the emergence of drug-resistant tubercu losis or hotspots of MDR tuberculosis. 69 Targeting these hotspots might be highly effective for controlling drug-resistant tuberculosis.…”
Section: Next-generation Molecular Epidemiologymentioning
confidence: 99%
“…A preliminary study from South Africa 151 found that Xpert MTB/RIF probe information, which differed substantially by geographical region, could be used for near real-time national surveillance using connected software, such as GXalert (open-source data connectivity for the GeneXpert). 152 By documenting the increasing frequency of a specific mutation, these data could be used for identifying the emergence of drug-resistant tubercu losis or hotspots of MDR tuberculosis. 69 Targeting these hotspots might be highly effective for controlling drug-resistant tuberculosis.…”
Section: Next-generation Molecular Epidemiologymentioning
confidence: 99%
“…In many countries in sub-Saharan Africa, access to mobile phones is nearly universal, and mHealth apps such as mobile data collection software and SMS are showing great promise for enhancing capacity in resource-constrained health systems [ 3 - 5 ]. For example, mHealth technologies can promote treatment adherence [ 6 - 10 ], enhance access to and uptake of maternal and child health care services [ 11 , 12 ], and improve the quality and reliability of services by connecting external quality assurance teams directly to diagnostic instruments [ 13 ]. However, mHealth studies have met with mixed success in achieving their aims in these settings: many interventions have been piloted, yet few have made it into routine practice [ 1 , 3 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, acceptability and satisfaction within the perception category were defined differently from one study to another [15,28-30,32,35,36,40,44]. Also, SMS-only intervention studies did not focus on technical outcome [12,15,22,29,30,32,35, 36,42,43,45,46] whereas studies involving other mHealth technologies such as an app or mobile data collection did so [21,28,33,37,39-41]. On the contrary, outcomes related to cost or cost-effectiveness were reported only via studies involving SMS [29,45,46].…”
Section: Resultsmentioning
confidence: 99%